2014
DOI: 10.1371/journal.pone.0089548
|View full text |Cite
|
Sign up to set email alerts
|

RAGE Regulates Immune Cell Infiltration and Angiogenesis in Choroidal Neovascularization

Abstract: PurposeRAGE regulates pro-inflammatory responses in diverse cells and tissues. This study has investigated if RAGE plays a role in immune cell mobilization and choroidal neovascular pathology that is associated with the neovascular form of age-related macular degeneration (nvAMD).MethodsRAGE null (RAGE−/−) mice and age-matched wild type (WT) control mice underwent laser photocoagulation to generate choroidal neovascularization (CNV) lesions which were then analyzed for morphology, S100B immunoreactivity and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 56 publications
(68 reference statements)
0
21
0
Order By: Relevance
“…This bimodal response according to the duration of diabetes may also reflect the altered expression levels of RAGE between 12 and 24 weeks. Further supporting evidence comes from Rage −/− mice subjected to laser-induced choroidal neovascularisation; these mice showed reduced lesion size alongside diminution of immune cell activation when compared with WT controls [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This bimodal response according to the duration of diabetes may also reflect the altered expression levels of RAGE between 12 and 24 weeks. Further supporting evidence comes from Rage −/− mice subjected to laser-induced choroidal neovascularisation; these mice showed reduced lesion size alongside diminution of immune cell activation when compared with WT controls [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that T cell production of S100B, although less than that of astrocytes, may, when polarized in the immunological synapse, be sufficient to trigger macrophage activation [ 49 ]. Recently S100B has been shown to be up-regulated in the eye in response to laser photocoagulation which generated choroidal neovascularisation [ 50 ]. Thus it is likely that S100B is present in the retina in EAU at the concentrations we have shown in vitro are able to influence macrophage response.…”
Section: Discussionmentioning
confidence: 99%
“…RAGE may also contribute to the activation of immune cells in laser-induced CNV lesion in a mouse model of AMD. 74 Choriocapillary vascular dropout and changes to choroidal thickness in AMD Upon assessment of the mean choroidal blood flow in patients at risk for CNV development, Grunwald et al 75 discovered an association between decreased circulation within the choroid and increased risk for wet AMD. These data implicate ischemia in CNV formation, and provide evidence for the importance of decreased choroidal blood flow in disease progression.…”
Section: Age-related Changes To Brmmentioning
confidence: 99%